Efek Pemberian Ekstrak Umbi Kembang Sungsang (Gloriosa superba L.) Pada Pembentukan Planlet Pisang (Musa paradisiaca L.) Kultivar Kepok Kunig Secara In Vitro - Julaiha Wahyu; Eti Ernawiati; Tundjung Tripeni Handayani; Sri Wahyuningsih (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
The world community, including Indonesia much like bananas because it has a relatively low price and good nutritional content. Banana kepok is a type of banana favored by the public because it tastes good and sweet. However, the obstacle that is often faced in kepok bananas is the difficulty in providing quality banana seeds quickly. Therefore, alternative technology is needed through tissue culture techniques. The purpose of this study was to determine the effect of adding breech flower tuber extract in culture media on the formation of banana plantlets of yellow kepok cultivar and to obtain scientific information about the growth profile of yellow kepok plantlets due to the addition of breech flower tuber extract to culture media. This research was conducted at the MTC Laboratory, PT. Great Giant Pineapple PG 4 Labuhan Ratu, East Lampung from December 2019 - April 2020 using a Completely Randomized Design (CRD) with ten replications consisting of the addition of 10% breech flower tuber extract as the primary treatment, 0.1% pure colchicine as a positive control, and without addition as a negative control. The results showed that the addition of 10% breech flower tuber extract in the culture media caused the growth of yellow kepok banana plantlets to be slower than the addition of 0.1% colchicine. Then in the media, with the addition of 10% breech flower tuber extract, the number of shoots, shoot height, number of better root and leaf area than the media without expansion, but 0.1% colchicine still showed the best results.